1997
DOI: 10.1016/s0020-7489(97)00030-8
|View full text |Cite
|
Sign up to set email alerts
|

Testing a model of absence and intent to stay in employment: a study of registered nurses in Malta

Abstract: This study used a cross-sectional, correlational design to test a model of absence and turnover of registered nurses developed from a review of the research literature (Gauci Borda and Norman, 1997). Testing the model involved comparing the relationship between job satisfaction, kinship responsibility, pay, employment opportunity, intent to stay in employment and absence for male and female registered nurses. All registered nurses (n = 254) working in clinical areas on a full-time shift basis, in one large gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
(27 reference statements)
2
21
0
1
Order By: Relevance
“…We observed that absenteeism at work was also higher among nurses being free from chronic conditions and showing lower levels of well-being. This finding is consistent with the results of majority of previous studies, confirming that greater job satisfaction is associated with lower levels of absenteeism at work [10,30]. Therefore, both our findings and data from literature point to a presence of a specific vicious circle: one's dissatisfaction with working conditions is reflected by higher level of his/her absenteeism, which in turn results in deterioration of working conditions of the remaining personnel; this stimulates reluctance to the colleagues who are too frequently on a sick leave.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that absenteeism at work was also higher among nurses being free from chronic conditions and showing lower levels of well-being. This finding is consistent with the results of majority of previous studies, confirming that greater job satisfaction is associated with lower levels of absenteeism at work [10,30]. Therefore, both our findings and data from literature point to a presence of a specific vicious circle: one's dissatisfaction with working conditions is reflected by higher level of his/her absenteeism, which in turn results in deterioration of working conditions of the remaining personnel; this stimulates reluctance to the colleagues who are too frequently on a sick leave.…”
Section: Discussionsupporting
confidence: 93%
“…It has further been suggested that unplanned absence is often short-term and sometimes voluntary [23]. Borda and Norman [37] in their study of nurses in Malta considered one-day or two-day absence frequency as a measure of ‘avoidable’ absence and related to job satisfaction, which was of concern in their study. Voluntary absence can also be planned as in the case of maternity [26] and annual [24] leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Married physicians and nurses were reported to have a lower absenteeism rate in Finland (Kivimaki et al, 2001) while, in Sweden, domestic responsibilities were reported to increase the possibility of absenteeism in female nurses (Borda and Norman, 1997) and, in Nigeria, married health professionals were more frequently absent from work due to domestic problems (Isah et al, 2008).…”
Section: Discussionmentioning
confidence: 99%